2022
DOI: 10.3389/fnins.2022.757316
|View full text |Cite|
|
Sign up to set email alerts
|

To Each Their Own: The Impact of Regulatory Focus on Consumers’ Response to Online Information Load

Abstract: Contrary to the common view that more information is always better, too much information can damage decision quality. Building on existing literature, this study identified regulatory focus as a critical factor influencing the effect of information load (IL) on online consumer decisions and used event-related potentials (ERPs) to uncover its underlying neural mechanism. Behavioral data showed that promotion-focused participants would spend less time making purchasing decisions in the low IL condition than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The study demonstrated that individuals with promotion focus tended to rely on intuition or direct cues from the surrounding environment to make decisions [ 41 ]. In contrast, individuals with promotion focus had higher cognitive demands, refined external knowledge more accurately, and recognized the nature of the information [ 58 , 59 ]. Thus, for the promotion focus group, when reading the domestic IPE events, they had a stronger sense of immersion and were more likely to recognize the essence of manipulation, so they were more likely to change their original willingness to accept recommended information, thus leading to a more significant change.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that individuals with promotion focus tended to rely on intuition or direct cues from the surrounding environment to make decisions [ 41 ]. In contrast, individuals with promotion focus had higher cognitive demands, refined external knowledge more accurately, and recognized the nature of the information [ 58 , 59 ]. Thus, for the promotion focus group, when reading the domestic IPE events, they had a stronger sense of immersion and were more likely to recognize the essence of manipulation, so they were more likely to change their original willingness to accept recommended information, thus leading to a more significant change.…”
Section: Discussionmentioning
confidence: 99%